Strategic improvisation, entrepreneurial self-efficacy and performance: The role of corporate entrepreneurship and organisational culture - Auwalu, Ibrahim Najafi (2017)
Global competition, dynamic environment and shrinking resources have created a lot of pressure on today’s organizations including Higher Education Institutions (HEIs). Hence, the need for effective human resource that is capable of not only ensuring efficient utilization of resources but also responding to rapid dynamism of today’s environment to enhance HEIs performance and relevance. Previous studies mainly concentrate on top management aspect of ensuring HEIs turn around, neglecting middle and lower level managers. Drawing from the Resource Base Theory (RBT) and Social Cognitive Theory (SCT), the study examines the indirect role of corporate entrepreneurship (CE) and organizational culture (OC) on the relationships between leaders’ strategic improvisation (SI), entrepreneurial self-efficacy (ESE) and performance. Data were generated from 229 academic leaders from ten HEIs in Kano, which were analyzed using PLS-SEM version 3.0. The findings of the direct relationship between SI, CE and performance were supported, while that of ESE reported an insignificant relationship, hence, rejected. Similarly, the result also indicates that CE depends on SI and ESE behaviour of academic leaders in HEIs. As postulated the mediating role of CE on SI, ESE and performance relationship was also established in the study. However, the moderating role of OC on the relationship between SI and performance and ESE and performance was not significantly established. The leaders’ SI, ESE, CE which were mainly used in private settings to explain performance is a novel contribution to knowledge and HEIs management. The finding is a wakeup call for HEIs management to identify and appreciate these factors in the study in order for them to play the needed role for national development. Future studies should include more samples as well as using organization as unit of analysis. The debate about the hierarchical level at which the strategic and entrepreneurial behaviour of managers is most beneficial is also another avenue for future studies.